EVALUATION OF MASTOID CAVITIES AFTER CANAL WALL DOWN MASTOIDECTOMY: Regulation of Neuropeptide Y - Khan, Amir Ali; Manzoor, Tahir; Shah, Amanat Ali; Ayub, Zeeshan (Pakistan Armed Forces Medical Journal, 2009)
Objectives: To evaluate mastoid cavities after canal wall down procedures in terms of: achieving a dry mastoid cavity, presence of residual or recurrent disease (Granulations and cholesteatoma). Study Design: Quasi-experimental study. Place and Duration of Study: The study was done in the ENT Department, CMH Rawalpindi Study was done in fourteen months from Nov 2006 to Jan 2008. Patients and Method: Fifty patients undergoing canal wall down mastoidectomy were included. Their mastoid cavities were evaluated for persistence of discharge and recurrence of granulations and cholesteatoma after the surgery. Results: After follow up period of 3 months, 8% patients had mild discharge, 12% had granulation and 2% patients had recurrence of cholesteatoma. Conclusion: Canal wall down mastoidectomies are very effective in controlling the recurrence of cholesteatoma, granulations formation and otorrhoea to a greater extent.